Bipolar AndrogenTherapy: The Rationale for Rapid Cycling of Supraphysiologic Androgen/Ablation in Men With Castration Resistant Prostate Cancer - Denmeade, Samuel R. (2010)
Androgen ablation is highly effective palliative therapy for metastatic prostate cancer but eventually all men relapse. New findings demonstrating that androgen receptor (AR) expression continues in androgen ablated patients has resulted in the classification “Castration Resistant Prostate Cancer” (CRPC) and has led to the development of new second-line “anti-ligand” hormonal agents. In this background is the paradoxical observation that the growth of some AR-expressing “androgen sensitive” human prostate cancer cells can be inhibited by supraphysiologic levels of androgens. This response may be due to effects of high-dose androgen on inhibiting re-licensing of DNA in cells expressing high levels of AR. It may also be due to recently described effects of androgen in inducing double strand DNA breaks. Based on available preclinical data described in this review demonstrating the effects of supraphysiologic levels of testosterone on inhibition of growth of CRPC xenografts, we initiated a clinical trial in men with CRPC testing the effect of monthly treatments with an intramuscular (IM) depot injection of testosterone. This IM formulation achieves supraphysiologic levels of testosterone that cannot be achieved with standard testosterone gel-based applications. The supraphysiologic testosterone level is followed by a rapid drop to castrate levels of testosterone with each cycle of therapy. This “bipolar androgen therapy” will not allow time for prostate cancer cells to adapt their AR expression in response to environmental conditions. The goal is to determine if a clinical response can be achieved through this non-adaptive rapid cycling approach in men with CRPC.